2020
DOI: 10.3390/nano10040665
|View full text |Cite
|
Sign up to set email alerts
|

Chemical- and Mechanical-Induced Lubrication Mechanisms during Hot Rolling of Titanium Alloys Using a Mixed Graphene-Incorporating Lubricant

Abstract: Hot rolling of titanium alloy currently is carried out without lubrication because of the surface defects. In order to explore an effective lubrication scheme to reduce friction and wear during hot rolling of titanium alloy, a mixed graphene-incorporating lubricant has been proposed to study its lubrication performance and mechanism. The tribological experiments were carried out by ball-disk friction and wear tester under hot-rolling parameters. Scanning electron microscopy (SEM), X-ray energy spectrum analyze… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…Moreover, Savenko and Karagioz [32] described that the plastic crumbling of the surface roughness can cause the rolling friction. Kong et al [33] suggested that the movement of wear debris in the wear scar may form an isolation layer, which partially transforms the sliding into rolling friction. In our case, MGO1 nanosheets may adsorb on some spherical wear debris and associate with them to convert the sliding friction into a combination of rolling friction and sliding friction, hence resulting in reduced friction coefficient.…”
Section: Tablementioning
confidence: 99%
“…Moreover, Savenko and Karagioz [32] described that the plastic crumbling of the surface roughness can cause the rolling friction. Kong et al [33] suggested that the movement of wear debris in the wear scar may form an isolation layer, which partially transforms the sliding into rolling friction. In our case, MGO1 nanosheets may adsorb on some spherical wear debris and associate with them to convert the sliding friction into a combination of rolling friction and sliding friction, hence resulting in reduced friction coefficient.…”
Section: Tablementioning
confidence: 99%
“…With the development of advanced machines, the working conditions of machines become more and more complicated, due to extreme pressure, high temperature, irradiation [ 1 , 2 , 3 , 4 , 5 , 6 , 7 ], etc. Friction and wear are the main reasons for the machine failure.…”
Section: Introductionmentioning
confidence: 99%
“…The use of graphene dispersed cutting fluid as an MQL application is not mentioned in this review. Kong et al [16] investigated the performance of graphene mixed lubricant in hot rolling of titanium alloy sheets. Friction coefficient decreased by 30-35% compared to dry friction condition and resulted in crack-free surface and reduced debris.…”
Section: Introductionmentioning
confidence: 99%